2018
DOI: 10.18280/ijht.360136
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of pressure drop and heat transfer in pin fin heat sink and micro channel pin fin heat sink

Abstract: Cooling of miniature size electronic components has become challenging for designer in the development of integrated circuits. Micro pin fin heat sink and Micro channel pin fin heat sink is one of the thermal management technique for effective cooling. The paper presents comparison of fluid flow and heat transfer characteristics for micro pin fin heat sink and micro channel pin fin heat sink with UN finned micro channel heat sink. A Three Dimensional heat sink with water as coolant subjected to constant heat f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The secondary flow enables the core flow to mix with the fluid near the wall to improve heat transfer efficiency. The cross-flow generated by the vortex can further reduce the thickness of the boundary layer (Saravanan et al, 2018;Al Muallim et al, 2020). The ribs on the side walls have a limited effect on the boundary layer of the flow channel, and the cooling performance is improved more significantly by the addition of ribs or vortex generator configuration at the bottom (Datta et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The secondary flow enables the core flow to mix with the fluid near the wall to improve heat transfer efficiency. The cross-flow generated by the vortex can further reduce the thickness of the boundary layer (Saravanan et al, 2018;Al Muallim et al, 2020). The ribs on the side walls have a limited effect on the boundary layer of the flow channel, and the cooling performance is improved more significantly by the addition of ribs or vortex generator configuration at the bottom (Datta et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of thermal transport in complex geometries with discrete heat sources is of major importance. The applications include disposal of nuclear wastes, electronic circuits, geothermal areas, food processing industries and cooling of electronic components [1][2][3][4][5]. A thorough understanding of thermal transport in complex geometries with discrete heat source is essential in the design of above equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Using particle swarm algorithm, they found that the thickness of fin is the most effective parameter on entropy generation. Also, in 2018, Saravanan et al [20] investigated pressure drop and heat transfer in a micro pin fin heat sink and a micro channel pin fin heat sink with different pin shapes including circular and square. In this study pin fins with staggered arrangement were studied numerically in Reynolds numbers ranging 100 to 900.…”
Section: Introductionmentioning
confidence: 99%